Mixing Performance Analysis of Cohesive Granular Particles in a Planetary Concrete Mixer Containing Two Different Mixing Units via DEM - Salamat, Jaber; Genç, Bülent (Orclever Science and Research Group, 2023)
In this paper, the mixing behavior of two different types of planetary concrete mixers is analyzed and evaluated in terms of homogeneity and granular particle velocity flow regimes. For this, the Hertz-Mindlin contact law, constant directional torque, and Simplified Johnson-Kendall-Roberts (SJKR) models are utilized via the Discrete Element Method (DEM). The Lacey mixing index was employed to calculate the mixing degree of granular particles to assess the mixing performance of planetary concrete mixers. Comparing the mixing degree, we have achieved a 45,5% improvement in the mixing period of high-quality homogeneous mixture in the model B mixer.